Readings for logical analysis - Hicks, Stephen R.C.; Kelley, David (W. W. Norton, 1998)
On torture and murder. On the causes of crime. On the death penalty. On the arts. On science. On education. On justice and rights. On economic freedom and government regulation. On abortion. On the existence of God.